'Towards a Conceptual Framework for Innate Immunity' - Twycross, Jamie; Aickelin, Uwe (Springer - Verlag, 2005)
Innate immunity now occupies a central role in immunology. However, artificial immune system models have largely been inspired by adaptive not innate immunity. This paper reviews the biological principles and properties of innate immunity and, adopting a conceptual framework, asks how these can be incorporated into artificial models. The aim is to outline a meta-framework for models of innate immunity.